ГРОМАДЯНСЬКЕ ВИХОВАННЯ МАЙБУТНЬОГО ФАХІВЦЯ З ЕКОНОМІКИ (Педагогіка вищої та середньої школи, 2010)
The paper addresses the problem of civic education of the students of the enomic university, identified and justified especially the formation of citizenship.